Psycholog szkolny wobec powrotu dzieci chorych przewlekle do szkoły – strategie zmiany postaw rówieśniczych - Nowakowska, Iwona (Studia Edukacyjne, 2018)
The aim of this article is to outline school psychologist’s interventions, which might be useful while supporting a chronically, somatically ill child in their re-entry to school, aiming at broadening their peers’ knowledge about the chronic disease and positively changing their attitudes towards the ill child. In the first part, the importance of peer relationships in childhood and adolescence, the relation of their quality to school absences and the positive role of school attendance in the process of adapta-tion to illness and recovery, are presented. Then, the arguments for school psychologist to become an agent of child’s positive school re-entry are provided. A framework of tasks to be performed by psy-chologist in the school setting is outlined. The second part focuses on the interventions which might be useful to meet expectations the environment has towards school psychologist in case of an ill child’s return to school. Among them, negative messages’ delivery, educational workshops design and deli-very, promoting self-advocacy of the child, preventing violence and supporting child’s siblings have been chosen as important areas of actions related to the child’s peers. A selection of suggestions how to deal with these diverse fields of activity has been outlined, basing on re-entry models, as well as on useful directions and interventions to prevent bullying and support children in developing psychoso-cial competences, which are discussed in research reports, metaanalyses and professional literature.